KNEE PAIN - SYMPTOMS, TREATMENT (Proceedings of International Educators Conference, 2024)
The knee joint is one of the most complex joints of the human body. Due to the constant weight on this "sophisticated" device, it is very weak, so everyone can experience this pain at least once in their life. The pain is dull, severe, even unbearable. Sometimes these pains occur only when a person walks or moves the legs, and sometimes they are felt constantly. The nature of pain in the knee joint and the factors that cause it can be different, more about them below.